The Trade Impact of the Covid-19 Pandemic - Xuepeng Liu; Emanuel Ornelas; Huimin Shi (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Using a gravity-like approach, we study how Covid-19 deaths and lockdown policies affected countries' imports from China during 2020. We find that a country's own Covid-19 deaths and lockdowns significantly reduced its imports from China, suggesting that the negative demand effects prevailed over the negative supply effects of the pandemic. On the other hand, Covid-19 deaths in the main trading partners of a country (excluding China) induces more imports from China, partially offsetting countries' own effects. The net effect of moving from the pre-pandemic situation to another where the main variables are evaluated at their 2020 mean is, on average, a reduction of nearly 10% in imports from China. There is also significant heterogeneity. For example, the negative own effects of the pandemic vanish when we restrict the sample to medical goods and are significantly mitigated for products with a high “work-from-home” share or a high contract intensity for products exported under processing trade, and for capital goods. We also find that deaths and lockdowns in previous months tend to increase current imports from China, partially offsetting the contemporaneous trade loss, suggesting that trade is not simply “destroyed,” but partially “postponed".
Keywords: F14; 330; trade flows; Covid-19; lockdown; stringency; China